An Examination of Context in the Age of Ubiquitous Mobile Computing. Issue 2 (10th February 2019) - Carl, Diana R.
Abstract: Mobile computing is widespread and is influencing human performance and learning. Its use occurs in many different contexts. The question arises as to how the access and use of content via mobile interacts with the different contexts and how this affects human performance and learning. This article considers research from three disciplines to identify impacts and recommend approaches to the development of learning and performance supports.